Pulsed laser deposition OF III-V semiconductor thin films: review - O.V. Devitsky (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов)
This review highlights the latest advancements in pulsed laser deposition of III-V semiconductor thin films on various substrates. The pulsed laser deposition method is shown to be highly effective and distinct from other thin film deposition techniques due to its discrete nature. Epitaxial growth of III-V thin films is crucial for developing new optoelectronic devices. The review presents experimental data on how various pulsed laser deposition parameters affect the structural, optical, and electrical properties as well as the stoichiometry of binary and multicomponent III-V thin films. It is demonstrated that achieving the highest structural quality in III-V thin films requires using femtosecond and nanosecond lasers with wavelengths ranging from 248 nm to 532 nm, a pulse energy density of no more than 3 J/cm², and substrate temperatures between 300 and 400°C. Additionally, the target material should be monolithic and have the highest possible density.